Morphometric Assessment and Condition Factor of the Mangrove Oyster from a tropical mangrove swamp, off Lagos Lagoon, South-West, Nigeria - Akinjogunla, Victoria Folakemi; Soyinka, Olufemi Olukolajo (Journal Omni-Akuatika, 2022)
The size composition, growth pattern and condition factor of One thousand, two hundred and sixty (1260) mangrove oyster - Crassostrea tulipa (C. tulipa) from the mangrove swamp, Lagos Lagoon were studied using recommended morphometric methods. The total shell length ranged from 1.5cm to 18.4cm, maximum width ranged from 1.5cm â€“ 10.4cm and the total weight was between 1.92g â€“ 132.1g. The oysters showed a unimodal size distribution. Also, there is strong significant correlation between the shell total length and the total flesh weight suggesting that an increase in length gives a corresponding increase in weight of an individual oyster. The total length-total weight and total weight-flesh weight relationships were positively correlated with calculated â€œbâ€ of 0.5826 and 0.5887 for combined sexes respectively. Negative allometric growth observed was verified from the b < 3 value. The condition factor of the oysters ranged between 6.5 and 10.5 for both male and female species indicating that the species are in good condition despite reported contaminations of the lagoon water.Keywords: Bivalve, C. tulipa, Lagos Lagoon, length-weight.